Analisis Keterlaksanaan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) pada Materi Struktur Atom dan Pengaruhnya terhadap Sikap Ilmiah Siswa Kelas X di SMAN 1 Kota Jambi - Fitria Mardiana Mardiana; Netti Yulia Ningsih (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to analyze the implementation of the Think Pair Share cooperative learning model on atomic structure material and its effect on students' scientific attitudes of class X students at Senior High School 1. Methodology: This study included a quasi-experiment. The sample is determined by a simple random sampling technique. The research instrument was in the form of an observation sheet. The data were analyzed to see the effect of the implementation of the TPS model on students' scientific attitudes using a linear regression test and a significance test with a t-test. Main findings: The implementation of the PjBL model is categorized as good, in terms of teachers and students, with an average of 81.25% and 74.78 %, respectively. Students' scientific attitude is categorized as good, with an average of 73.97% for three meetings. The correlation test results between students' implementation of the TPS model and students' scientific attitudes were obtained r = 0.707. The results of the study proved that the implementation of the TPS-type cooperative learning model went well, and there was an influence between the implementation of the TPS-type cooperative learning model and the students' scientific attitude on atomic structure material for class X at Senior High School 1. Novelty/Originality of this study: The update in research is to complement previous research by proving that the TPS-type cooperative learning model affects students' scientific attitudes. Students' scientific attitude is essential to be developed in the current era of globalization.